Transplantation: desensitization and survival in kidney transplant recipients - Süsal, Caner; Opelz, Gerhard (Nature reviews. Nephrology, 2017)
Elimination of donor-specific antibodies against HLA has been used to enable transplantation of HLA-incompatible kidneys from living donors. In contrast to two previous US studies, a UK study now reports that desensitization does not offer a survival benefit over remaining on the waitlist for a compatible organ.